Pengaruh Kepercayaan dan Komitmen terhadap Loyalitas Pelanggan dengan Kepuasan sebagai Variabel Moderasi (Studi Kasus pada PT. Mitra Jofer Indonesia) - Nuraeni, Siti; Yulia, Iis Anisa; Putra, Mulyana Gustira (Jurnal EMT KITA, 2025)
The purpose of this study is to analyze the impact of Trust and Commitment on Customer Loyalty, considering Satisfaction as a variable that can moderate the relationship. This study involved all customers of PT Mitra Jofer Indonesia as many as 45 companies. The sampling technique used is the census method in the Non-Probability Sampling category. Hypothesis testing was carried out using multiple linear regression and moderation regression analysis. The findings of this study indicate that Trust and Commitment have an influence on Customer Loyalty. In addition, Satisfaction is proven to strengthen the influence of Trust on Loyalty, but has no moderating effect on the relationship between Commitment and Loyalty.